Association between severity of sepsis and thyroid function profile - Siampa, Vindy Nugraha; Abadi, Satriawan; Aman, Andi Makbul; Bakri, Syakib; Halim, Risna; Zainuddin, Andi Alfian (Acta Biomedica Atenei Parmensis, 2023)
Background and aim: Critical illness conditions such as sepsis are often accompanied by altered hormone levels, which may result in decreased thyroid axis activity. This condition aims to provide metabolic substrates for vital organs such as the brain and immune system. Significant alteration of the thyroid axis in critical illnesses such as sepsis known as Low-T3 Syndrome which is associated with increased mortality. This study aims to determine the association between severity of sepsis and thyroid function profile as a predictor of mortality in sepsis patients. Methods: An observational study involving 62 subjects with sepsis and septic shock. Serum was measured using Enzyme-linked Immunosorbent Assay (ELISA) method. Statistical analysis used Mann-Whitney, Kruskal-Wallis, and Spearman’s correlation tests. Statistical test results are significant if the p-value <0.05. Results: The median fT3 level was lower in the septic shock group 13.94 pg/ml (7.71-19.93) compared to the sepsis group 20.15 pg/ml (11.08-37.15) where there was a significant difference (p<0.001). There was a significant correlation between The Sequential Organ Failure Assessment (SOFA) score and fT3 levels (R: -0.270, p=0.032). The non-survivor group had a lower median fT3 level 16.56 pg/ml (7.71-30.03) compared to the survivor group 17.50 pg/ml (10.32-37.15) where there was a significant difference (p<0.036). Conclusion: Based on the severity of sepsis, the more severe the sepsis condition, the lower thyroid function levels are obtained where decreased thyroid function levels can be a prognosis indicator to predict mortality in sepsis patients.